Irisin and inflammatory cytokines in elite male rowers: adaptation to volume-extended training period - Jürimäe, J.; Purge, P. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: This study examined the effect of 6-month volume-extended training period on irisin and inflammatory cytokine concentrations in elite male rowers. METHODS: Nine elite male rowers (25.3±6.5 yrs; 190.6±5.1 cm; 93.4±7.5 kg; 14.6±2.6% body fat; maximal oxygen consumption [VO2max]: 64.0±3.5 mL/min/kg) participated in this study. Body composition, VO2max and blood biochemical markers were assessed before and after training period. Venous blood samples were analyzed for irisin, interleukin (IL)-2, IL-4, IL-6, IL-8, IL-10, vascular endothelial growth factor, interferon-Gamma, tumor necrosis factor-a, IL-1a, IL-1ß, monocyte chemoattractant protein-1 and epidermal growth factor (EGF). RESULTS: Average weekly training volume was significantly higher (P<0.05) during the 6 months of heavy training compared to relative rest (11.6±1.4 h/week vs. 18.4±1.0 h/week), while training intensity remained the same. At the end of training period, body fat% was significantly decreased, and fat free mass and maximal aerobic power significantly increased. Irisin was not changed (P>0.05) as the result of 6-month heavy training period, while training induced significant (P<0.05) increases and decreases in IL-10 and EGF values, respectively. CONCLUSIONS: Serum irisin concentration was not sensitive to a significant increase in weekly training volume during the volume-extended training period in elite male rowers. An increase in training stress was accompanied by the increase in IL-10 and a decrease in EGF levels, and these inflammatory cytokines could be regarded as markers of heavy training stress during the typical preparatory period in elite male rowers.